Are Digital Marketing Trends and Challenges Aligned with SDGs?: A Review of Indonesian SMEs - Ekaputra, Adriansyah; Sari, Ratna Deli; Yuniarsih, Yuyun; Algunadi, Muhammad (Yayasan Sinergi Kawula Muda, 2024)
This paper provides a comprehensive literature review to explore the prevailing trends and obstacles in digital marketing for Indonesian Small and Medium Enterprises (SMEs) with respect to the Sustainable Development Goals (SDGs). This study employs a literature review method to identify the current trends and challenges in digital marketing for Small and Medium Enterprises (SMEs) in Indonesia and how these align with the Sustainable Development Goals (SDGs). The research approach used is descriptive qualitative. This study aims to fill the gap in existing research by providing a comprehensive analysis of the alignment of digital marketing practices with the SDGs among Indonesian SMEs. It examines how digital marketing strategies can aid in fulfilling the SDGs, focusing on aspects such as economic growth, innovation, and sustainable consumption. By meticulously analyzing existing literature, the study identifies prominent digital marketing trends, significant challenges encountered by Indonesian SMEs, and insights on how digital marketing can foster sustainable development. The results are intended to offer valuable insights for policymakers, practitioners, and academics in the realm of digital business.